The Confluence Of Politics And Traditional Religion Among The Iban In Elections In Sarawak - Stanley Bye, Kadam-Kiai (Institute of Borneo Studies, UNIMAS, 2016)
The longhouse symbolizes the livelihood strategy of the Iban and acts as the custodian of the community’s values, norms, adat (custom), system of belief, tradition and culture. The Iban strictly follow their adat when undertaking new initiatives or adopting new livelihood strategies like embarking on a bejalai or a journey of fortune. Before embarking on or adopting a new livelihood strategy, the Iban will perform a miring (process of giving offering) and a blood sacrifice ceremony where chants are uttered asking the petara (god) to guide them in their new endeavour as they seek happiness and fortune. The miring ceremony is to prevent the person from encountering bad omen, to appease the petara (god) and to boost his confidence. At the end of the miring ceremony and after the sacrifice is done, the piring (offering) will be smeared with the blood of a rooster, as usually a rooster is sacrificed. Amulets and charms too will be smeared with the blood of the rooster. Miring ceremony can be performed for virtually any significant activities that the Iban wish to undertake such as before starting a new padi season. Today, many Iban politicians adopted the practices in their political activities.